TRENDS AND PROSPECTS FOR DEVELOPMENT OF THE EU's COMMON AGRICULTURAL POLICY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - T. Kalashnikova; A. Kalashnikov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The transformational changes in the EU's common agricultural policy have been researched and the conscious, consistent, purposeful and gradual movement of the EU member states towards the implementation of the principles of sustainable development has been determined. A comprehensive analysis of the key features of the 2013 EU's common agricultural policy reform has been carried out. It has been determined that the EU's CAP has become more object-oriented, integrated and complementary; aimed at bringing the EU's agricultural sector closer to the world market, gradual reduction of the CAP budget and the burden on the EU budget, strengthening of market principles in relations between the agricultural producers and the EU. It has been revealed that tools introduced by the reform include environmentally-addressed direct payments, co-financing, mechanisms of external and internal convergence, and contribute to the environmental management resolution of corresponding problems, but the socioeconomic problems of the industry are not sufficiently solved. The main imperatives of the EU's common agricultural policy for the period of 2021-2027 have been determined: socioeconomic, environmental, political, human development. The analysis of possible scenarios of EU's CAP development after 2010 deserves attention. It is substantiated that the key issues in the development of the new EU's CAP will be: continuation by the EU member states of the chosen course to deepen the foundations of sustainable development; quantitative parameters of the financial security of the EU's CAP as a result of Brexit; on what basis will the distribution of EU's CAP resources be made among member states. Particularly important issue will be the choice of tools and support directions of the CAP, since it will determine the EU's CAP EU model parameters for almost a decade.